PENGARUH PEMBAYARAN PAJAK DAERAH TERHADAP PELAYANAN PEMERINTAH DAERAH KOTA PALEMBANG - Sugiharto Sugiharto; Dimas Pratama Putra (Universitas Tridinanti, 2022)
This research aims to determine and analayze the effect of local tax payment on government services in the city of Palembang. The research method used in this study is a qualitative descriptive wih associative problem formulation. The population used in this study were all employees in the sub- district of kertapati taken wih purvosive sampling method as many as 40 employees by filling out a questionnaire. The technique used in this research is linear regression. Based on the result of this research, regional tax payments influence local government services in the city of Palembang, this can be seen from the results of the t-test that the significance is smaller than 0.05, which means Ho is rejected and Ha is accepted. The correlation coefficient which states the closeness of the relationship are strong and positive at 0.736. With a coefficient of determination of 0.541 or 54.1 percent, the rest is influenced by other variables not examined in this research. The conclusion of this reserch states that the hypothesis which states that local tax payments influence local government services in the city of Palembang is acceptable. Keywords: Payment of Local Taxes, Local Government Services